Neuromuscular, physiological and endocrine responses to a maximal speed training session in elite games players - Johnston, M.; Cook, C. J.; Crewther, T.; Drake, D.; Kilduff, L. P. (European Journal of Sport Science, 2015)
The aim of this study was to determine the acute neuromuscular, biochemical and endocrine responses to a maximal speed training (MST) session. Eighteen male rugby players completed the protocol, which involved performing six maximal effort repetitions of 50 m running sprints with 5 minutes recovery between each sprint. Testosterone (T), cortisol (C), creatine kinase (CK), lactate (La), perceived muscle soreness (MS) and counter movement jump were collected immediately pre (PRE), immediately post (IP), 2 hours post (2P) and 24 hours post (24P) the sprint session. A bimodal recovery pattern was observed from the jump parameters with several declining significantly (p = 0.05) IP, recovering 2P and suffering a secondary decline 24P. CK and perceived MS were elevated IP and continued to rise throughout the protocol, while La was only elevated IP. T and C were unaffected IP but showed significant declines 2P. These data indicate that MST results in a bimodal recovery pattern of neuromuscular function with changes most likely being related to metabolic and biochemical responses.